Pengaruh Model Pembelajaran Carousel Feedback Terhadap Kemampuan Literasi Sains Mata Pelajaran IPA Kelas 3 Sekolah Dasar - Aryani, Devi; Ariefka, Reza (LPPPI Publishing, 2025)
This study aims to analyze the effect of the Carousel Feedback learning model on the scientific literacy skills of grade 3 students of Rejodadi Elementary School in science subjects. The research method used is pre-experiment design with a One-Group Pretest-Posttest. The research sample consisted of 23 students selected through probability sampling techniques. The research instrument was a science literacy test that had been tested for validity and reliability. The results showed a significant increase in students' average scores, from 57.17 (pretest) to 68.26 (posttest). The Paired Sample T-Test statistical test showed a significance value of 0.000 (<0.05), which indicated a significant effect of the Carousel Feedback learning model on students' scientific literacy. Thus, this learning model can be an effective alternative to improving scientific literacy in elementary schools.